PENERAPAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR DAN SIKAP SISWA SMP NEGERI 2 LHOKSEUMAWE - Rohaida .; Rahmah Johar; Jarnawi Afgani Dahlan (Universitas Syiah Kuala, 2013)
This study aims to assess the difference in learning outcomes of students who receive realistic mathematics learning approach with those who obtain the conventional one. The study is conducted using pre-test post-test control group design with the entire population of eighth grade students of SMP N 2 Lhokseumawe as sample. In this study, purposive sampling technique is used for sampling. Data collection is conducted by giving test and non- test. The test includes cognitive testing on circle after the treatment is given , and the non – testis given using questionnaire to measure students’ attitude and response towards the realistic mathematics learning. Furthermore, the statistical test used in this study is the t-test. The data also illustrates that it follows the normal curve and it is homogenous. In order to test the hypothesis using the t-test, df (degree of freedom)= n1 + n2 - 2 = 30 + 31-2 = 59. As a result, it is obtained that t t table is 3.502 1.671 . In conclusion, the study finds that 1 ) the students who receive realistic mathematics learning approach perform better on the test compare to those who do not receive the treatment (2 ) Students’ response towards realistic mathematic approach is positive